Improving Student Literacy and Environmental Care Movement in Pematang Raya Village, Raya Sub-District, Simalungun Regency - Ritonga, Fajar Utama; Sinaga, Warisman; Utomo, Budi (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Increasing student literacy and environmental care for elementary and junior high school students is the theme of the Real Work Lecture/Kuliah Kerja Nyata (KKN) Group 138 in Pematang Raya Village, Simalungun Regency. This paper aims to describe the community service activities carried out by Universitas Sumatera Utara students in KKN activities in increasing Merdeka Belajar Kampus Merdeka Outcome Base Education (MBKM-OBE) as a forum for providing opportunities for students to experience off campus, interact, identify social phenomena and provide solutions through Project Base Learning and Problem Solving for the community around the location of the Real Work Lecture/Kuliah Kerja Nyata (KKN) carried out by the Community Service Institute of Universitas Sumatera Utara. From the results of observations and assessments of students, the priority scale of the problem is the lack of student literacy and low environmental awareness. The implementation method is carried out during the 2 months students are at the KKN location by making KKNT posts, learning houses and programs that have been compiled and run regularly every week for 2 months. The results of the 138 KKN group service can be seen in real changes, namely increasing student literacy to read as a means of filling spare time, doing homework independently and conscious activities to dispose of waste in its place, sorting organic and non-organic waste and being able to make simple compost.